On the microstructure and corrosion behavior of Fe-28.5Ni steel subjected to severe plastic deformation - Melika Jalali; Hamid Reza Jafarian; Ali Shanaghi; Ali Reza Eivani (Journal of Materials Research and Technology)
This study investigates the influence of the Accumulative Roll-Bonding (ARB) process on the corrosion behavior of Fe-28.5Ni alloys. The research examines how the ARB as a severe plastic deformation technique alters the microstructure and corrosion resistance of this alloy. Specimens subjected to different ARB cycles were analyzed using electrochemical impedance spectroscopy, cyclic potentiodynamic polarization, and open-circuit potential measurements in 1 M HCl solution. Results indicate that increasing the number of ARB cycles initially decreases corrosion resistance due to higher dislocation densities. However, after four cycles, the formation of low-angle grain boundaries enhances corrosion resistance by creating a more uniform surface energy distribution and stable corrosion product layers. Optimal corrosion resistance was observed at six ARB cycles, beyond which high-angle grain boundaries began to diminish the protective effects. This study underscores the significance of optimizing ARB parameters to improve the performance of Fe–Ni alloys in corrosive environments.